Methodological proposal to obtain agroecosystem sustainability indicators from a multidimensional and systemic approach - Tonolli, Alejandro Javier (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2019)
Agroecosystems are human-made ecosystems to obtain products and services of their own interest. In this manner, the ecosystems come into being agroecosystems. Therefore, in order to describe, understand or intervene on them, it is necessary to observe emerging biological properties and attributes related to social, economic, cultural and institutional aspects. At the same time, if these agroecosystems are to be analyzed in terms of sustainability, in addition to contemplating the different dimensions that integrate it, a systemic perspective must be taken into account in the conceptual and operational constructions that allow sustainability indicators to be obtained. In this sense, the present work reviews and classifies the different forms exposed in the bibliography to obtain indicators and shows the scarcity of proposals that operate with a systemic perspective in order to resolve the tension between production and conservation which swings around the idea of sustainability. Taking all this into account, a methodological proposal alternative is presented to obtaining indicators of aroecosystems sustainability, which operates conceptually and empirically from a multidimensional and systemic perspective by contrasting the state of the agroecosystem, in each of its dimensions, with the demands established by the sustainability of these dimensions. Finally methodological considerations about its use are made and advantages and limitations of its application are highlighted.